Improving Digitalization Ability of AI (Assembler Edu) for Economic Teacher Meeting (MGMP) In Semarang, Central Java - Widiyanto; Rusdarti; Sakitri, Wijang (Universitas Negeri Semarang, 2024)
The era of digitalization requires teachers in Indonesia to be more creative and present learning media in the classroom. However, not all teachers are able to use it. The aim of this study is to provide an overview of training that can improve teachers' digitalization abilities. The training was conducted by doing pre-test, giving materials, practicing the use of media, discussing the materials and doing post test. After carrying out initial observations, in-depth observations and pre-tests and post-tests, it was found that the training could increase understanding of Chat GPT, paint 3 D, AR and digitalization. The participants could operate Chat GPT to create storyboard outlines for the purposes of preparing learning media in the Entrepreneurship class, the participants were also able to create 3D and AR using Assembler Edu. In the future, the training should be conducted regularly as technology develop fast.